Field Dependence/Independence, Impulsivity/Reflectivity, Gender, and Cloze Test Performance of Iranian EFL Learners: A Study of Relations - Rastegar, Mina; Honarmand, Nazanin Mehrabizadeh (European Scientific Journal, ESJ, 2016)
This study aimed at exploring any significant relationships among field dependence/independence, impulsivity/reflectivity, and cloze test performance of Iranian EFL learners, and attempted to seek any significant differences between males and females regarding their field dependence/independence, impulsivity/reflectivity, and cloze test performance. Participants were 72 (47 females and 25 males) Iranian EFL university students in ShahidBahonar University of Kerman. Group Embedded Figures Test (GEFT) by Witkin et al. (1971), Impulsivity subscale of Impulsiveness, Venturesomeness, and Empathy (IVE) scale by Eysenck and Eysenck(1978), and a cloze test consisting of two cloze passages (Oller& Perkins, 1980) were utilized to obtain the required data.To statistically analyzethe data, the statistical procedures of Pearson Product Moment Correlation and Independent Samples T-test were utilized using SPSS version 21. The findings of this study indicated that field independence had a significant positive correlation with reflectivity, and field dependence also had a significant positive correlation with impulsivity. However, the findings revealed no significant relationship between cloze test performance and any of other variables. It was also found that females are more reflective and males tend to be more impulsive.